Pediatric Enterococcal Bacteremia: A 12-Year Retrospective Study in a French Pediatric Center. Issue 9 (14th July 2022) - Bizot, Etienne; Truong, Jeanne; Mariani-Kurkdjian, Patricia; Bonacorsi, Stephane; Faye, Albert; Caseris, Marion
Abstract : Background: Enterococcal bloodstream infections (EBSIs) are rare infections in children associated with 5%–10% of mortality in previous studies. The recent evolution of antimicrobial resistance and therapies require updated data. Methods: We conducted an observational retrospective study between January 2008 and December 2019 describing the characteristics of children with EBSI in a French pediatric hospital. All positive Enterococcus spp. blood cultures associated with sepsis symptoms were analyzed. We also compared characteristics of healthcare-associated infections (HAIs) and community-acquired infections (CAIs) and described antimicrobial resistance evolution during this period. Results: In total 74 EBSI were included. Enterococcus faecalis was the most common pathogen (n = 60/74, 81%) followed by Enterococcus faecium (n = 18, 24%), including 4 enterococcal coinfections. EBSIs were mainly associated with central-line associated infection (38%), surgical site infection (14%) or urinary tract infection (11%). An underlying disease was present in 95.9%. However, 4 patients died in the month following the EBSI resulting in a 5.4%, 30-day mortality. All were HAI. HAI (84% of EBSI) was associated with longer bacteremia [31% persistent bacteremia (more than 3 days) versus 0% for CAI; P = 0.029] and more antimicrobial resistance. Amoxicillin resistance is increasing since 2013 in E. faecium (63% in 2013–2019), although high-level gentamicin resistance is stable (19%). Only 1 EBSI due to vancomycin-resistant Enterococcus was described in our cohort, who died. Conclusions: EBSIs are rare infections in children mostly described in children with underlying disease. Healthcare-associated bacteremia is associated with higher rates of resistance and poorer prognosis, requiring the involvement of pediatric infectious disease specialists to improve management.